Pengaruh Pupuk Kotoran Ayam Terhadap Pertumbuhan Dan Hasil Jahe Pada Tanah Aluvial - -, Misnadeh (Fakultas Pertanian Universitas Tanjungpura, 2019)
Productivity of ginger (Zingiber officinale) in Indonesia are generally low, this may be related to several factors such as less optimal fertilization, unsuitable environmental conditions to grow, both climate and soil fertility, as well as the use of non recommended cultivation techniques. The aims of this study was to determine the effect of Cattle Chicken Manures on The Growth and Yield of Ginger on alluvial soil. The experiment was conducted at the from April until Juni 2018. The research design used in this study was Completely Randomized Design with 5 levels Cattle Chicken Manures The treatments were the use of P1 = 10 ton/ha , P2 = 15 ton/ha, P3 = 20 ton/ha, P4 = 25 ton/ha, P5 = 30 ton/ha. Each treatment was repeated five times, and the experimental unit consisted of 4 plant samples. Varieties of ginger used came from farmer